(untitled) (TAJ: Journal of Teachers Association, 2018)
Idiopathic Intracranial Hypertension is a disease of unknown aetiology common in obese females and presents with headache, papilledema, raised CSF opening pressure, no abnormalities in CSF examination and no abnormality on CT scan or MRI of the Brain. Sinovenous abnormalities are commonly detected in patients of IIH by different neuroimaging techniques. But the exact role of these sinovenous abnormalities in the causation of the disease or whether they are an effect of the disease is not yet known. Nor has a ‘gold standard’ investigation been established yet for detection of the sinovenous abnormalities. This study was done to detect the presence of sinovenous abnormalities in IIH patients by performing a Magnetic Resonance Venography of the brain. All 33 patients of IIH who presented to Rajshahi Medical College Hospital during the study period from June 2009 to May 2010 were included in the study. There were 30 females and 3 males having a F:M ratio of 10:1. 91% of the patients were between 20 and 35 years of age and most of them were married housewives. 63.64% patients had history of use of oral contraceptives. Unusually 51.52% of the patients had a BMI less than 25 indicating that they were not even overweight (BMI 25 to 30). Only 6% of the patients had BMI > 30 indicating that they were obese. Headache and papilloedema were present in all patients but visual difficulties were present only in 54.54% of the patients. Abnormalities in MRV of the brain were detected in 27.27% (9/33) of the patients and transverse sinus hypoplasia was the commonest finding (88.89% - 8/9 patients). There was no statistically significant difference in the findings of MRV abnormalities between the males and females or among the patients having BMI less or more than 25 TAJ 2013; 26: 53-56